Correspondence of Japanese War Prisoners in Camps of People’s Commissariat for Internal Affairs-Ministry of Internal Affairs of the USSR (1945-1956): Review of Domestic and Foreign Historiography - S. V. Serebrennikov (Научный диалог)
For the first time the features of lighting by domestic and foreign researchers the correspondence of Japanese prisoners of war in the camps of the People’s Commissariat for Internal Affairs-Ministry of Internal Affairs of the USSR (1945-1956) are considered. The article contains a historiographical analysis of the work of historians of Russia, Kazakhstan, Switzerland, Japan, published in the period from 1992 to 2017, which in varying degrees covered the correspondence of Japanese prisoners of war. Data on various aspects of the topic contained in the theses and monographs, scholarly articles by Russian and foreign researchers are identified and analyzed. The author pointed out that to date, despite the large number of scientific papers on Japanese prisoners of war, any work is not published devoted to the correspondence of the Japanese prisoners of war in camps in the Soviet Union. Nevertheless, the question reflects in dissertations, monographs, scientific articles on foreign prisoners of war of World war II in the Soviet Union. However, the analysis of historians’ coverage of Japanese prisoners of war correspondence with family and friends is undertaken in this article for the first time. Both achievements and understudied aspects of the problem are identified. A number of issues and promising directions that require further study are revealed.